On Identities in Algebras Q_n,λ Generated by Idempotents - Rabanovych, V. I.; Samoilenko, Yu. S.; Strilets, O. V. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We investigate the presence of polynomial identities in the algebras Q_n,λ generated by n idempotents with the sum λe (λ ∈ C and e is the identity of an algebra). We prove that Q_4,2 is an algebra with the standard polynomial identity F_4, whereas the algebras Q_4,2, λ ≠ 2, and Q_n,λ, n ≥ 5, do not have polynomial identities.